What remains [videorecording (DVD)] : the life and work of Sally Mann - Cantor, Steven; Spirer, Peter; Mann, Sally, 1951- (Zeitgeist Films, 2008)
Director Steven Cantor examines the life and work of photographer Sally Mann in a follow-up documentary to his earlier "Blood Ties", also included on this disc.